2023
DOI: 10.1021/acssuschemeng.3c00389
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biodegradable Nanoparticulate Chain-End Functionalized Polyhydroxybutyrate–Caffeic Acid with Multifunctionalities for Active Food Coatings

Abstract: The bioactivities of polyhydroxyalkanoates have been curtailed owing to the lack of bioactive functional groups in their backbones. In this regard, polyhydroxybutyrate (PHB) produced from new locally isolated Bacillus nealsonii ICRI16 was chemically modified for enhancing its functionality, stability as well as solubility. First, PHB was transformed to PHB-diethanolamine (PHB-DEA) by transamination. Subsequently, for the first time, the chain ends of the polymer were substituted by caffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The melting temperature (T m ) observed in the study performed by Tripathi et al, 45 exhibited that PHB obtained from chloroformhypochlorite extraction was found to be 179°C. According to reports by Abdelmalek et al, 46 the TGA profiles indicate that the maximum degradation temperature for PHB is 290°C. This process involves the cleavage of C-O and CP%O bonds, along with the breakdown of crystalline regions.…”
Section: Discussionmentioning
confidence: 88%
“…The melting temperature (T m ) observed in the study performed by Tripathi et al, 45 exhibited that PHB obtained from chloroformhypochlorite extraction was found to be 179°C. According to reports by Abdelmalek et al, 46 the TGA profiles indicate that the maximum degradation temperature for PHB is 290°C. This process involves the cleavage of C-O and CP%O bonds, along with the breakdown of crystalline regions.…”
Section: Discussionmentioning
confidence: 88%
“…A 3.0 mg amount of each sample was placed in an aluminium pan and heated at a rate of 10 • C/min from −10 • C to 200 • C for DSC analysis. The point of inflection in the DSC curve between the onset and offset temperatures reveals the glass transition temperature and the melting point, which was reported as the endothermic event's peak temperature [35].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…PHB modification reactions are important to prepare new PHB derivatives for some industrial and medical applications ( Hazer, 2010 ; Hazer et al, 2012 ; Guennec et al, 2021 ). Some of them are halide derivatives ( Arkin and Hazer, 2002 ; Yalcin et al, 2006 ; Erol et al, 2020 ), chitosan derivatives ( Arslan et al, 2007 ), diethanol amine derivatives ( Tuzen et al, 2016 ), trithiocarbonate derivatives ( Hazer et al, 2020 ), methyl salicylate derivatives ( Hazer et al, 2021 ), ricinoleic acid derivatives ( Ullah et al, 2024 ), PEG derivatives ( Hazer et al, 1999 ; Wadhwa et al, 2014 ), and caffeic acid derivatives ( Abdelmalek et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…PHB is a commercially available biodegradable natural aliphatic polyester for some biomedical applications, such as implant biomaterials, tissue engineering, and food packaging applications ( Chen and Zhang, 2018 ; Mehrpouya et al, 2021 ; Abdelmalek et al, 2023 ). PHB derivatives can be used as novel biodegradable adsorbents for analytical applications ( Wadhwa et al, 2014 ; Unsal et al, 2015 ; Tuzen et al, 2016 ; Altunay et al, 2020 ; Ullah et al, 2024 ; Ali et al, 2024 ) for drug delivery systems ( Bayram et al, 2008 ; Kılıcay et al, 2011 ; Kilicay et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%